2020
DOI: 10.4067/s0718-48162020000100039
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de la tiroidectomía total en el tratamiento del hipertiroidismo

Abstract: La autora declara no tener conflictos de interés.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…En este tipo de casos, el tratamiento quirúrgico ha sido el de mayor acogida, aunque se ha evidenciado discrepancia de opiniones con respecto a implementar tratamiento farmacológico, pero debido al avance en los casos de bocio endotorácico se ha optado por la tiroidectomía total para extracción de nódulos. La gran mayoría de personal médico defiende este tipo de procedimiento debido al crecimiento acelerado de nódulos a nivel de tiroides, pero así mismo en ocasiones se opta implementarla cuando hay manifestaciones clínicas que avalen la evolución o cuando se evidencia criterios de malignidad (Pardo M, 2020;Wémeau et al, 2022).…”
Section: Discussionunclassified
“…En este tipo de casos, el tratamiento quirúrgico ha sido el de mayor acogida, aunque se ha evidenciado discrepancia de opiniones con respecto a implementar tratamiento farmacológico, pero debido al avance en los casos de bocio endotorácico se ha optado por la tiroidectomía total para extracción de nódulos. La gran mayoría de personal médico defiende este tipo de procedimiento debido al crecimiento acelerado de nódulos a nivel de tiroides, pero así mismo en ocasiones se opta implementarla cuando hay manifestaciones clínicas que avalen la evolución o cuando se evidencia criterios de malignidad (Pardo M, 2020;Wémeau et al, 2022).…”
Section: Discussionunclassified
“…From the previous evidence it can be seen that regarding treatment with (TT), it is intended to demonstrate its efficacy, but it reflects how 26.9% of the patients studied have shown a therapeutic failure, which leads us to compare this treatment with the others studied, and it is reflected that despite its high effectiveness, the failure threshold is much higher than in the treatments with (ADT) and (131I), obtaining these as described by the authors Azizi F, et Malboosbaf R. in one and Zhao Lina et al l in another article respectively summarized in the results, with 19.1% failure in terms of antithyroid drugs and 22.3% in treatment with radioactive iodine (131I). 18,24,27 For treatment with radioactive iodine (131I), each investigation has decided to take a variable as the field of investigation in relation to hyperthyroidism, and as each of these has established percentages making relevance to the effects of the treatments, that is where it is generates our task, in observing which of these could give the best solution to the need in question. 20,24,26 Now, in this demonstration we find 6 articles, in the first place, we will stick to highlighting the results in common, where their effectiveness is exposed since only 22.3% are shown that they have not achieved the success of the treatment causing a hypofunction of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%